1990
DOI: 10.1002/ajh.2830350115
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cell surface glycoprotein CD9 (P24) antigen on megakaryocyte lineage leukemias and cell lines

Abstract: We herein describe CD9 (p24) antigen as existing on the cell surface of megakaryocyte lineage leukemias as well as megakaryocytic leukemia cell line, MEG-01 and HEL, by means of fluorescence-activated cell sorter (FACS IV) with a panel of monoclonal antibodies (Mabs). We found CD9 antigen expression on the cell surface of megakaryoblastic leukemias as well as MEG-01 and HEL cells. Furthermore, CD9 antigen expression increased while culturing these cells with phorbol esters, and was also found in the cytoplasm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In order to define the location of the plasma membrane more clearly, the cells were treated with an antibody against the CD-9 protein, that is located on the plasma membrane in a number of cell types. 24,33 Immunofluorescence images of LNCaP cells treated with the anti-CD-9 antibody revealed a clear location of the CD-9 protein at the plasma membrane of cells transfected with pCMV-EGFP-TRPL (Fig 3b) and cells transfected with pCMV-EGFP-C1 (Fig 3e). Overlay of the CD-9 and EGFP-TRPL images for each cell transfected with pCMV-EGFP-TRPL showed that the EGFP-TRPL chimeric protein and the CD-9 protein are colocated at the plasma membrane in a band (about 30-50% of the plasma membrane) of the cell (Fig 3c, indicated by the orange color (arrows)).…”
Section: Expression Of the Trpl Protein In Transiently Transfected Lnmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to define the location of the plasma membrane more clearly, the cells were treated with an antibody against the CD-9 protein, that is located on the plasma membrane in a number of cell types. 24,33 Immunofluorescence images of LNCaP cells treated with the anti-CD-9 antibody revealed a clear location of the CD-9 protein at the plasma membrane of cells transfected with pCMV-EGFP-TRPL (Fig 3b) and cells transfected with pCMV-EGFP-C1 (Fig 3e). Overlay of the CD-9 and EGFP-TRPL images for each cell transfected with pCMV-EGFP-TRPL showed that the EGFP-TRPL chimeric protein and the CD-9 protein are colocated at the plasma membrane in a band (about 30-50% of the plasma membrane) of the cell (Fig 3c, indicated by the orange color (arrows)).…”
Section: Expression Of the Trpl Protein In Transiently Transfected Lnmentioning
confidence: 99%
“…24 Briefly, cells were fixed and blocked as described above. Then cells were incubated with 1:40 dilution of anti-CD-9 antibody at 41C overnight and anti-mouse IgG secondary antibody conjugated with Cy3 (1:400 dilution) for 2 h at room temperature.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…On the basis of these findings, the sample was suggestive of acute myeloid leukaemia probably of megakaryoblastic origin. To characterize this type of myeloproliferative disorder accurately, samples from bone marrow were submitted for flow cytometry analysis 1–5 . The immunological panel (Table 2) revealed immunoreactivity for 7.2% CD3 (T lymphocytes), 5.8% CD79 (panB‐lymphocytes), 2.3% CD34 (blast cells), 4.0% CD14 (monocytes), 64.5% CD9 (platelets), 59.5% CD61 (platelets) and 17.7% CD18 (beta2‐integrins).…”
Section: Case Reportmentioning
confidence: 99%
“…CD9 is expressed on a wide variety of cells; within the megakaryocytic lineage CD9 is already expressed during the early stages and therefore can contribute to the diagnosis of AML-M7. 222, 223 For the last antibody position, CD25 was chosen, as some data suggest that this marker is expressed during the early stages of megakaryocytic development. 224 Furthermore, CD25 can be used to detect immunophenotypic aberrant mast cells when a systemic mastocytosis or chronic eosinophilic leukemia (possibly in combination with an AML or MDS) is suspected.…”
Section: Introductionmentioning
confidence: 99%